Characteristics of Comments in Social Media - I Gusti Ngurah Parthama (e-Journal of Linguistics, 2025)
Negative and sarcastic sentiments dominate online discourse. It reflects the dynamic nature of digital communication and its socio-linguistic implications. This study investigates the prevalence and types of comments with focusing on explicit negative opinions and sarcastic and explicit opinions. Those emerge as the most frequent forms in sentiment discourse. Drawing upon insights from sentiment analysis frameworks by Liu (2015) and Ponzi et al. (2017), this research categorized user comments and analyzed their frequencies and implications within the context of social media interactions. The research employs qualitative analysis to classify and interpret comments. It also combines theoretical insights with real user-generated content. Comments were grouped into categories, including fact-implied opinions, explicit negative opinions, sarcastic opinions, and implicit opinions. It reveals significant trends in the expression of dissatisfaction and humor-laden critiques online. The findings suggest that digital platforms serve as spaces for users to openly voice grievances. It is often through direct negativity or sarcasm. In particular, sarcasm functions as a creative linguistic tool for indirect critique and identity construction. While it also reflects broader societal concerns such as socioeconomic inequality. These trends highlight the polarized and emotionally charged nature of online discourse, where negativity is amplified through rapid interactions and shared cultural references. Implications of this study underline the importance of nuanced sentiment analysis models that account for the complexities of tone, sarcasm, and indirect communication. Additionally, fostering constructive digital environments requires strategies to mitigate negativity. While it is promoting balanced engagement and contributing to a deeper understanding of evolving digital communication practices and societal dynamics.